Optimal Growth with Scale Economies in the Creation of Overhead Capital - Weitzman, M. L. (Review of Economic Studies, 1970)
Journal Article Optimal Growth with Scale Economies in the Creation of Overhead Capital Get access M. L. Weitzman M. L. Weitzman Cowles Foundation Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 4, October 1970, Pages 555–570, https://doi.org/10.2307/2296485 Published: 01 October 1970 Article history Received: 01 May 1969 Revision received: 01 December 1969 Published: 01 October 1970